The Smoking Paradox in Stroke Patients Under Reperfusion Treatment Is Associated With Endothelial Dysfunction - Iglesias-Rey, Ramón; Custodia, Antía; Alonso-Alonso, Maria Luz; López-Dequidt, Iria; Rodríguez-Yáñez, Manuel; Pumar, José M.; Castillo, José; Sobrino, Tomás; Campos, Francisco; Silva-Candal, Andres da; Hervella, Pablo (Frontiers in Neurology, 2022)
Objective This study aimed to explore the association between smoking habit and the serum levels of soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK), in relation with the functional outcome of patients with acute ischemic stroke undergoing reperfusion treatment. Methods Observational and retrospective study of a series of patients with acute ischemic stroke subjected to reperfusion treatments. Clinical, analytical, and neuroimaging parameters were analyzed. The main endpoint was the functional outcome at 3 months, measured by the modified Ranking Scale (mRS). Logistic regression models were used to analyze the association between smoking and sTWEAK levels with functional outcome and leukoaraiosis. Results The results showed that smoking habit was associated with a good functional outcome at 3 months in patients with stroke (OR: 3.52; 95% CI: 1.03–11.9; p = 0.044). However, this independent association was lost after adjusting by sTWEAK levels (OR 1.73; 95% CI: 0.86–13.28; p = 0.116). sTWEAK levels were significantly lower in smoker patients [4015.5 (973.66–7921.83) pg/ml vs. 5,628 (2,848–10,202) pg/ml, p < 0.0001], while sTWEAK levels were significantly higher in patients with poor functional outcomes at 3 months [10,284 (7,388–13.247) pg/ml vs. 3,405 (2,329–6,629) pg/ml, p < 0.0001]. Conclusion The decrease in sTWEAK levels was associated with a good functional outcome in smoker patients with stroke undergoing reperfusion therapy.